Word Skepticism and Word-magic in Afanasy Fet’s Poetry - Hajnády, Zoltán (Slavica, 2022)
This paper is devoted to Afanasy Fet’s philosophy of art. In Fet’s poetry, the virtuosic use of words is combined with linguistic skepticism, involving a feeling of verbal inexpressibility and the apotheosis of silence. The topic of his poetry is the inexpressible and unspeakable, which, paradoxically, becomes expressible and describable through impressionistic imagery, metaphoric nomination, musical effects, and metalinguistic means. Fet’s poems are highly polysemic, and the semantic implications of his texts are inexhaustible.